2008
DOI: 10.2134/jeq2007.0141
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Nitrogen Sorption to Soils in the Presence of Poultry Litter‐Derived Dissolved Organic Matter

Abstract: Two environmental aspects associated with land application of poultry litter that have not been comprehensively evaluated are (i) the competition of dissolved organic matter (DOM) and P for soil sorption sites, and (ii) the sorption of dissolved organic nitrogen (DON) relative to inorganic nitrogen species (e.g., NO(3)(-) and NH(4)(+)) and dissolved organic carbon (DOC). The competition between DOM and P for sorption sites has often been assumed to increase the amount of P available for plant growth; however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Along with the reduction in odor, pathogens, and weeds, composting also immobilizes highly mobile NO 3 − in the litter to its slow-release form [9][10][11]. It is also easier to handle, store, transport, and apply litter that has been composted [12].…”
Section: Introductionmentioning
confidence: 99%
“…Along with the reduction in odor, pathogens, and weeds, composting also immobilizes highly mobile NO 3 − in the litter to its slow-release form [9][10][11]. It is also easier to handle, store, transport, and apply litter that has been composted [12].…”
Section: Introductionmentioning
confidence: 99%
“…The EON stock only peaked in the seasons when chicken manure applied (Fig. 3), likely due to the direct input of EON from manures (Goyne et al, 2008) since the chicken manure is rich in EON (Table 2). EON stocks decreased obviously with the enhancement of irrigation in the later periods of vegetable growth.…”
Section: Discussionmentioning
confidence: 99%
“…Other forms of leachable N, especially EON, have been suggested to be taken into account when evaluating N leaching risk due to its large contribution to N migration in the soil profile (Bhogal et al, 2000;Khalili and Nourbakhsh, 2012;Siemens and Kaupenjohann, 2002). Especially in greenhouse soils, often-applied manures may be a direct source of EON subject to leaching loss (Goyne et al, 2008). Hence, simultaneous investigation of accumulation and migration of nitrate and EON is needed to better understand the scale and the dynamics of N migration and leaching loss in greenhouse soils.…”
mentioning
confidence: 99%
“…The chemically mediated oxidation-reduction potential may alter the chemical and physical characteristics of the soil including local pH increases, leading to increased dissolution of soil organic matter. Studies have shown that sorption is governed by competing sorbates as dissolved organic matter (DOM) in ligand exchange, as well as pH and ionic strength [18][19][20]32,33]. In addition, as redox potential decreases further, soils/sediments release manganese Mn 2+ and iron Fe 2+ via the microbiological and chemical reduction of metal oxides [18,19,34].…”
Section: Introductionmentioning
confidence: 99%